Menganalisis Potret Industri Indonesia Berdasarkan Industri Pengolahan Migas dan Non-Migas - Erwin Putra Rasul Dafana; Riska Putri Dinarti; Muhammad Yasin (Universitas 45 Surabaya, 2024)
This research aims to analyze industrial conditions in Indonesia with a focus on the oil and gas processing industry (oil and gas) and non-oil and gas industries. This study uses a descriptive approach by collecting secondary data from various official sources such as the Central Statistics Agency (BPS), the Ministry of Industry, and the annual reports of related companies. The analysis results show that the oil and gas and non-oil and gas processing industries have a significant contribution to the Indonesian economy, but face different challenges. The oil and gas industry, although it plays a large role in state revenues and exports, experiences fluctuations in world oil prices which affect its stability. On the other hand, the non-oil and gas industry shows more stable and diversified growth, with sectors such as manufacturing, textiles and electronics being the main pillars. This research also identifies various factors that influence the development of these two types of industry, including government policy, foreign investment, and infrastructure. It is hoped that these findings can provide insight for policy makers and stakeholders in formulating strategies to advance industry in Indonesia.